2010
DOI: 10.1021/la1037519
|View full text |Cite
|
Sign up to set email alerts
|

Conductometric and Light Scattering Studies on the Complexation between Cationic Polyelectrolyte Nanogel and Anionic Polyion

Abstract: This work aims to provide a basic understanding of the water dispersibility of a 1:1 stoichiometric polyelectrolyte complex (SPEC) in water in the absence of low-molecular-weight salts. We studied the complexation of a linear polyanion, potassium poly(vinyl alcohol sulfate) (KPVS), with a cationic polyelectrolyte nanogel (CPENG) composed of a lightly cross-linked copolymer of N-isopropylacrylamide and 1-vinylimidazole, in an aqueous salt-free solution (pH 3 and 25 °C), as a function of the molar mixing ratio (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…More recently, the same group analyzed the water dispersibility of complexes formed between cationic polyelectrolyte nanogels and anionic polyions and their complexation by conductometric and light scattering studies, respectively. , …”
Section: Cationic Micro/nanogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, the same group analyzed the water dispersibility of complexes formed between cationic polyelectrolyte nanogels and anionic polyions and their complexation by conductometric and light scattering studies, respectively. , …”
Section: Cationic Micro/nanogelsmentioning
confidence: 99%
“…Recently, Kokufuta and Doi , reported a study on the water dispersibility of a 1/1 stoichiometric complex between a cationic nanogel and linear polyanion (SPENC) composed of a cross-linked (using MBA as the cross-linker) copolymer of 1-vinylimidazole and NIPAM and discussed in terms of the association–dissociation reactions between both of the polyelectrolyte components. The results indicated that the whole and a part (segment) of the complexed polyanions undergo dissociation–association reactions on the surface of a SPENC particle, depending on the ionization state of the cationic gel component.…”
Section: Cationic Micro/nanogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium alginate (SA), extracted from sea weeds having (1,4)-linked β-Dmannuronate(M) and α-L-glucuronate (G) residues is widely used in the food packaging (Oliveira Filho, Rodrigues, Valadares, Almeida, Lima, Takeuchi, et al, 2019;Yao, Zhou, Chen, Ma, Li, & Chen, 2018), drug delivery (Agüero, Zaldivar-Silva, Peña, & Dias, 2017), textile (Li, He, & Huang, 2017), and cosmetic fields (Bae, Nam, & Park, 2019), among others. Owing to its polyanionic nature, SA can form PECs with positively charged polymers in the absence of organic solvents (Doi & Kokufuta, 2011;Paques, van der Linden, van Rijn, & Sagis, 2014). Based on these advantages, SAbased PECs are commonly used as bone tissue engineering scaffolds, drug packaging/controlled release agents, and functional food additive carriers (Mirpoor, Hosseini, & Yousefi, 2017;Xiao, Yu, & Yang, 2011;Zimet & Livney, 2009).…”
Section: Introductionmentioning
confidence: 99%